Multicenter Retrospective Analysis of Implant Overdentures Delivered with Different Design and Attachment Systems: Results Between One and 17 Years of Follow-Up - Marco Tallarico; Luca Ortensi; Matteo Martinolli; Alessio Casucci; Emiliano Ferrari; Giuliano Malaguti; Marco Montanari; Roberto Scrascia; Gabriele Vaccaro; Pietro Venezia; Erta Xhanari; Ruggero Rodriguez y Baena (MDPI AG, 2018)
Purpose: To analyze implant and prosthetic survival rates, complications, patient satisfaction, and biological parameters of patients rehabilitated with implant overdentures (IOV) on splinted and nonsplinted implants and different attachment systems, in function for one to 17 years. Methods: This retrospective study evaluated data collected from patients rehabilitated with implant overdentures between January 2001 and December 2016 in nine different centers. Outcome measures were implant and prosthetic success rates, mechanical complications, marginal bone loss (MBL), oral health impact profile (OHIP), bleeding on probing, and plaque index. Results: A total of 581 implants were installed in 194 patients. Patients were followed for a mean period of 60.6 months (range 6⁻206). Eighty-nine patients received 296 low profile attachment (OT Equator), 62 patients received 124 ball attachments, and 43 patients received 107 Locator attachments. In eighty-three patients the implants were splinted with computer aided design/computer aided manufacturing (CAD/CAM) or casted bar. At the last follow-up, 10 implants failed in eight patients. Statistical significance was found for failed prostheses (P = 0.0723) and complications (P = 0.0165), with better values for splinted implants. No statistically significant differences were found in proportion of implant and prosthetic failure (P > 0.05). At a five-year follow-up, proportion of complications (P = 0.0289) and failed prostheses (P = 0.0069) were statistically higher for IOV on Locator attachments. No difference was founded in MBL at one- and two-year follow-up between different attachment systems (P > 0.05). Statistically significant improvement in all the OHIP categories was reported in all the patients, after one year of function. Conclusions: Implant overdenture showed high implant and prosthetic survival rates, low complications, high patient satisfaction, and good biological parameters in the long-term follow-up. Splinting the implants may reduce number of mechanical complications. Locator attachments showed higher number of complications. Further studies are needed to confirm these preliminary results.